Effects of foam rolling and static stretching on ankle dorsiflexion and jumping ability: a randomized controlled trial - Patti, Antonino; Thomas, Ewan; Giustino, Valerio; Rossi, Carlo; Paoli, Antonio; Drid, Patrik; Palma, Antonio; Bianco, Antonino (Biology of Sport, 2025)
This study aimed to assess the impact of a 5-week intervention that combined foam rolling (FR) and static stretching (SS) on ankle dorsiflexion range of motion (ROM). Furthermore, the study evaluated the influence of the intervention on leaping ability utilizing the counter movement jump test (CMJ). Random assignment was used to allocate fifty-one amateur sports enthusiasts to either the foam rolling + static stretching (FR-SS) group ( n = 22; age: 19.3±6.87 years; height: 171±7.91 cm; weight: 66.7±9.52 kg) or the static stretching (SS) group ( n = 29; age: 18.5±4.60 years; height: 171±11.5 cm; weight: 68.3±16 kg). A baseline assessment (T0) and an assessment following the 5-week intervention (T1) were carried out. An inertial sensor was used to quantify the ankle joint ROM, and an optical detecting system was used to measure the CMJ performance. Significant differences were found between T0 and T1 in the FR-SS group. Significant group-by-time interaction effects (F = 14.44; p < 0.001, η 2 p = 0.128) and between-subject effects (F = 53.5; p < 0.001, η 2 p = 0.353) were found. Significant enhancements in CMJ performance ( p < 0.01) were noted after the intervention in the FF-SS group. A similar trend was not observed in the SS group. Our findings suggest that a 5-week intervention combining FR with SS leads to greater improvements on ROM and angular velocity of the ankle joint, and on CMJ performance compared to SS alone. If further research confirms these results, FR and SS could be widely used in sports and rehabilitation.